The Branded Hotel as an Element of Destination Branding - Abiola-Oke, Elizabeth (Academica Turistica - Tourism and Innovation Journal, 2019)
The purpose of this article was to examine the effect of the availability of hotel brands in a destination on the promotion of the destination. Data for this study were collected through online questionnaires from a diverse population. The respondents were reached via a social medium (LinkedIn, on which the author has an account) and membership in different tourism-related and non-tourism related groups. The tourism-related groups are made up of both professionals in the field and nonprofessionals. The data were analysed using descriptive analysis (tables, cross tabulation, and Spearman ranked correlation) with spss. It was discovered that hotel brands have little impact on the choice of destination to visit in comparison to other elements of a destination, such as attraction, transportation, and other supporting services. Therefore, a hotel brand cannot be used as the sole element of destination branding as it has little or no effect on branding a destination.
Keywords: Hotel branding; Destination Branding; Destination Marketing; Destination Promotion